The synergistically enhanced activity and stability of layered manganese oxide via the engineering of defects and K+ ions for oxygen electrocatalysis. Issue 12 (4th March 2022) - Zhou, Zihao; Zheng, Xiaoying; Huang, Hongyun; Wu, Yanli; Han, Shengbo; Cai, Weixiong; Lan, Bang; Sun, Ming; Yu, Lin
Abstract : A layered MnO2 rich in defects and interlayered K + ions is designed and applied as an efficient electrocatalyst for the zinc–air battery. The synergistic effect of defects and K + ions enhances the ORR activity/stability and assists the OER activity. Abstract : Structural defects and interlayered ions are two classic aspects that can regulate the electrochemical activities of layered manganese oxides. However, the synergistic effect of defects and interlayered ions and how this works are rarely reported in the field of oxygen electrocatalysis. Moreover, it is difficult to control activity and stability in a defect-rich layered manganese oxide. Herein, we report a defect- and K + -rich layered manganese oxide (K–DMO) and reveal the synergistic effect of defects and K + ions on enhancing the activity and stability during oxygen reduction/evolution. It is found that the synergistic effect improves the electrochemical performance via optimizing the reaction mechanism and kinetics. K–DMO exhibits superior activity and stability, and its use in a rechargeable zinc–air battery results in excellent rechargeability, with a narrow voltage gap of 0.66 V between the charge and discharge platforms, a high peak power density of 139.9 mW cm −2, and extremely long-term stability over 1000 cycles at 5 mA cm −2 . In short, the identification of a synergistic effect provides a blueprint for controlling the activity and stability of layered materials.